2014
DOI: 10.1371/journal.pone.0113320
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Emphysema Heterogeneity on Pulmonary Function

Abstract: ObjectivesTo investigate the association between emphysema heterogeneity in spatial distribution, pulmonary function and disease severity.Methods and MaterialsWe ascertained a dataset of anonymized Computed Tomography (CT) examinations acquired on 565 participants in a COPD study. Subjects with chronic bronchitis (CB) and/or bronchodilator response were excluded resulting in 190 cases without COPD and 160 cases with COPD. Low attenuations areas (LAAs) (≤950 Hounsfield Unit (HU)) were identified and quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 24 publications
5
24
0
Order By: Relevance
“…Ju et al showed that greater degree of lobar heterogeneity of emphysema on single-volume CT images was associated with less airflow obstruction. 31 We extend these findings by demonstrating that image-matching based measures of biomechanical heterogeneity (Jacobian and strain CVs) are predictive of lung function, and these biomechanical changes are provided on a lobar and sub-lobar basis. It is pertinent to note that the Jacobian CV and strain CV are more strongly associated with the prediction of the Cat CT category, one in which there is significant CT emphysema but the spirometric abnormality remains relatively masked.…”
Section: Discussionsupporting
confidence: 56%
“…Ju et al showed that greater degree of lobar heterogeneity of emphysema on single-volume CT images was associated with less airflow obstruction. 31 We extend these findings by demonstrating that image-matching based measures of biomechanical heterogeneity (Jacobian and strain CVs) are predictive of lung function, and these biomechanical changes are provided on a lobar and sub-lobar basis. It is pertinent to note that the Jacobian CV and strain CV are more strongly associated with the prediction of the Cat CT category, one in which there is significant CT emphysema but the spirometric abnormality remains relatively masked.…”
Section: Discussionsupporting
confidence: 56%
“…3840 The extent of emphysema was defined as the percentage of low attenuation areas (%LAA) relative to the total lung volume. To reduce overestimation of the percentage of emphysema possibly caused by image noise or artefact, small clusters of pixels below the −950 HU thresholds were removed.…”
Section: Methodsmentioning
confidence: 99%
“…However, within an organ, diseases display a large degree of spatial heterogeneity , with the same organ containing both healthy and pathological regions [610]. Thus, some NCs may appear to efficiently target an organ, but it remains unknown if those NCs in fact target the pathological subregions rather than the nearby healthy regions.…”
Section: Introductionmentioning
confidence: 99%